Characterization of the genes coding for two major cell wall proteins from protein-producing Bacillus brevis 47: complete nucleotide sequence of the outer wall protein gene. - Tsuboi, A (1986)
Bacillus brevis 47 contains two cell wall proteins termed the outer wall protein (OWP) and middle wall protein (MWP), each of which forms hexagonal arrays in the cell wall. A 6-kilobase BglII-BclI fragment of B. brevis 47 DNA cloned into Bacillus subtilis with a derivative of pHW1 as a vector directed the synthesis of a polypeptide, with almost the same molecular weight as the authentic OWP, as judged by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, which was specifically recognized by the anti-OWP antibody. Nucleotide sequence analysis of the subfragment revealed that it contains two open reading frames in tandem. The upstream truncated open reading frame corresponds to the carboxy-terminal portion of the MWP, and the downstream open reading frame corresponds to the entire translational portion of the OWP. The latter encodes a secretory precursor of the OWP, consisting of a total of 1,004 amino acid residues with a signal peptide of 24 amino acid residues at its amino-terminal end. Futhermore, analysis of transcripts in B. brevis 47 suggests that the MWP and OWP genes, in that order, constitute a cotranscriptional unit and that the major promoter shared by the two genes is located upstream of the MWP gene.